Data Warehouse Design in Academic Environment - Munawar, Munawar (Lembaga Penerbitan Universitas Esa Unggul, 2014)
The popularity of Data Warehouses (DW)sfor data analysis has grown tremendously, asconventional transaction processing systems have matured, becoming faster and more stable. Conventionalsystems in universitiesworking in the same area, storedaily activities and display or report these events on a regular basis. Therefore, the establishment of the DWs will help the top management in the development of strategies and take appropriate decisions inthese universities.This paper addresses issues related to designing a DW for private university in Jakarta. The purpose of the project isto provide a process model that will enhance decision making capabilities ina private university in order to facilitate and improve academic activities.Ã‚Â Keywords: requirements analysis, conceptual design, data warehouse, academic